Jak się filozofuje z siodła? Przypadek Michela de Montaigne’a - Krupecka, Iwona (Zoophilologica. Polish Journal of Animal Studies, 2020)
In this text I am collecting and interpreting Michel de Montaigne’s reflections on the horses and horse-riding. I argue that there are two basic problems in which this theme was used by Montaigne: the fragility and unexpectedness of human life and body-mind relation. In both fields Montaigne proposed a re-evaluation in relation to the classical culture. In the first one, by interpreting Plato’s “practice of death” as an art of exposing oneself to an unexpected, and in the second, by linking mind activity with the bodily processes.